Influence of external magnetic field on the tribological performance of magnetic fluids in different lubrication regimes - Xiaoyu Wang; Yan Zhao; Huanchen Liu; Xiaobo Wang; Wenjing Lou; Jun Yang (Friction, 2025)
Magnetic fluids (MFs) represent a unique class of smart functional lubricating materials, with their physical properties tunable by the application of a magnetic field. In this study, stable MFs were prepared with varying mass fractions of Fe3O4 nanoparticles. The influence of magnetic field on their tribological behaviors was examined on a modified rotational rheometer in both boundary and mixed lubrication regimes. The results show that the magnetic field significantly enhances the tribological performance of the MFs, especially for boundary lubrication. In particular, for the MF containing 1 wt% Fe3O4 nanoparticles, a friction reduction of 41.2% and a wear volume reduction of 94.7% were achieved in the presence of a magnetic field. Post-analysis of the worn surfaces was carried out with multiple techniques to gain deeper insights into the lubrication mechanisms. In the boundary lubrication regime, the magnetic field aids in introducing a larger amount of Fe3O4 nanoparticles into the contact, leading to the formation of a more continuous deposit film.